Case Report: "Striving to Skip the Withdrawal" Using Buprenorphine–Naloxone Microdosing for Hospitalized Patients. Issue 4 (December 2019) - Martin, Leslie; Lennox, Robin; Regenstreif, Lori; O'Shea, Timothy
Abstract : ABSTRACT: Opioid substitution therapy is a life-saving, first-line treatment for patients with opioid use disorder. It is a key intervention to prevent further mortality and morbidity during the opioid crisis that is claiming lives across Canada. Traditionally, patients must be experiencing at least moderate withdrawal in order to safely initiate buprenorphine–naloxone, which is recommended as first-line therapy for the treatment of opioid use disorder. Across Canada, physicians have been "microdosing" buprenorphine–naloxone in order to "skip the withdrawal" required for traditional inductions. However, the role of these protocols in acutely ill hospitalized patients has not been explored in the literature. We describe 2 cases where microdosing protocols were utilized in the management of hospitalized patients with both an acute medical issue and active opioid use disorder. This article explores special considerations when managing hospitalized patients with microdosing protocols, including case selection, timing, titration schedules, and the development of a therapeutic alliance. Abstract : N/A: Le traitement de substitution aux opioïdes est un traitement de première ligne qui permet de sauver des vies chez les patients présentant un trouble de l'utilisation des opioïdes. Il s'agit d'une intervention clé pour prévenir davantage de mortalité et de morbidité durant la crise des opioïdes faisant de nombreuses victimes au Canada. Traditionnellement, les patients doivent subir un sevrage au moins modéré pour pouvoir prendre en toute sécurité de la buprénorphine-naloxone, recommandée en tant que traitement de première intervention du traitement du trouble de l'usage des opioïdes. Partout au Canada, les médecins utilisent le «microdosage» du buprénorphine-naloxone afin d'«éviter le sevrage» requis pour les inductions traditionnelles. Cependant, le rôle de ces protocoles chez les patients hospitalisés en phase aiguë n'a pas été exploré dans la littérature. Nous décrivons deux cas dans lesquels des protocoles de microdosage ont été utilisés dans la gestion de patients hospitalisés présentant à la fois un problème médical aigu et un trouble actif d'utilisation d'opioïdes. Cet article explore les considérations spéciales lors de la gestion des patients hospitalisés avec des protocoles de microdosage, y compris la sélection des cas, le choix du moment, les calendriers de titrage et le développement d'une coalition thérapeutique.